Hospital pharmacovigilance's role in managing Stevens-Johnson syndrome: a case report - Alan Maicon DE OLIVEIRA; Fabiana Rossi VARALLO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Stevens-Johnson syndrome is a condition that is considered rare but of severe intensity, potentially induced by medications, with antimicrobials being highlighted as the main culprits. We present a case of an older individual who developed the syndrome, overlapping with Toxic Epidermal Necrolysis, likely due to the use of the drug ciprofloxacin. During hospitalization, the case was managed by the pharmacovigilance sector (I. Systematization of scientific evidence in health; II. Conducting an in-depth investigation of the experienced case, comparing data with scientific information; III. Studying the causality of the adverse reaction; IV. Developing a protocol of practices to be followed, team training, and monitoring of the steps; V. Organizing notification and referral to responsible regulatory agencies) and a multidisciplinary team. Treatment was based on health evidence; however, there was refractoriness to clinical measures, and the patient progressed with worsening skin shedding, infection, cardiac arrest, and death after the resuscitation protocol. In addition to the factors mentioned above, other aspects contributed to the severity of the episode: presence of multimorbidity, advanced age, late seeking of healthcare assistance, and continued use of the drug that induced the reaction, even after the initial symptoms. ANVISA categorized the event as severe and reportable to the Uppsala Monitoring Centre. The hospital pharmacovigilance service collaborated with the multidisciplinary team, contributing to the prompt and appropriate management of the event, risk management, and Health education. This study provides content for multiprofessional learning, strategies for safety, and person-centered care.